Effectiveness of NGO-Led Livelihood Initiatives on Income Generation among Rural Women of Bihar - KOMAL KRITI; Dr. (Mrs.) AARTI SINGH; Sanghamitra Mohapatra (Indian Journal of Extension Education, 2025)
The study explored the effectiveness of NGO-Led livelihood initiatives on income generation among rural women of Bihar. 450 rural women from 3 districts of Bihar were selected and data was collected during the year 2023-24. This study adopted a descriptive approach, using structured close-ended questionnaires through quantitative analysis involving interviews and surveys to collect information. Key activities such as tailoring, farming, handicrafts, homestead farming, and animal husbandry saw high engagement rates, with tailoring being the most popular at 97.33%. These initiatives significantly improved household financial stability, as evidenced by increased income, expenditure, and savings across all sectors. Tailoring, for instance, boosted average income from Rs 7,600 to Rs 16,000, while savings more than doubled. Similarly, papad-making, handicrafts, and animal husbandry demonstrated substantial profitability and improved resource management. Farming recorded the highest income increase, with a mean rise from Rs 54,742.83 to Rs 76,733.54, supported by a highly significant t-statistic of 13.91. Overall, the findings underscore the success of NGO-Led livelihood initiatives in promoting sustainable livelihoods and financial resilience among rural women in Bihar.